Case Report: Advanced pulmonary sarcomatoid carcinoma with adrenal gland metastasis after sintilimab combined with anlotinib treatment - Dai, Gangyi; He, Lang; Yan, Qin; Li, Yamao; Huang, Yuandong; Li, Bin; Wang, Guoping (Frontiers in Oncology, 2023)
Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of non-small-cell lung cancer (NSCLC), which is resistant to conventional chemotherapy and radiotherapy with a poor prognosis. The MET inhibitor may be effective for the patients with MET exon 14 skipping mutation. This mutation was not detected in this patient. However, the PD-L1 TPS 60%, KRAS and TP53 mutations were detected in this patient could benefited from immunotherapy. The anlotinib is a novel multitarget antiangiogenic drug that could be effective for advanced non-small-cell lung cancer and some sarcoma patients. We report a patient with advanced pulmonary sarcomatoid carcinoma successfully treated with immunotherapy combined with antiangiogenic drugs.